Preliminary experience of stent-assisted coiling of wide-necked intracranial aneurysms with a single microcatheter - Park, Keun Young (BMC Neurol, 2019)
BACKGROUND: The purpose of this study was to report our preliminary experience of stent-assisted coiling (SAC) of wide-necked intracranial aneurysms with a single microcatheter in patients with parent arteries that were small-caliber, with stenosis, or a very tortuous course. METHODS: Between March 2018 and December 2018, we treated 394 aneurysms in 359 patients with endovascular treatment. Among 197 aneurysms treated by SAC, there were 16 cases (all wide-necked unruptured aneurysms) treated by SAC with a single microcatheter and a Neuroform Atlas stent. Follow-up angiography was performed at 6 to 12 months after SAC, and clinical follow-up was performed from 6 to 12 months in all patients. RESULTS: The reasons for SAC with a single 0.0165-in. microcatheter were small-caliber (n = 4), stenosis (n = 2), and very tortuous course (n = 10) of the parent arteries. There was no complication related to delivering or deploying the Neuroform Atlas stent as well as no failure of selecting aneurysm by cell-through technique. All patients had a modified Rankin score of 0 at discharge and at follow-up. Initial angiographic results showed six cases (37.5%) of complete occlusion. In follow-up angiographies, 12 cases (75.0%) achieved compete occlusion. CONCLUSION: When performing SAC of wide-necked intracranial aneurysms in parent arteries with small-caliber, stenosis, or a very tortuous course, cell-through SAC using a single microcatheter and a Neuroform Atlas stent within a 5 Fr- (or smaller) guiding or intermediate catheter might be a useful option.